RENDAKU PADA GABUNGAN LEKSEM DALAM BAHASA JEPANG (KAJIAN MORFOFONEMIK) - Dumaria, Viska (Japanese Literature, 2013)
This Thesis research about changes the sound of the rendaku that occurs in the merger word namely reduplication and composition of japanese. Rendaku is the phenomenon in morfofonemik regulating the change of sounds that occur from voiceless consonants to became voiced consonants. Change the sound of this is not merely a change in which every single consonant voiceless to be voiced consonants, but change the sound by adding dakuten or a modifier of the sound (‘’) on the phoneme first of second components in the merging of the word. The aim of this research is described how can rendaku could happen and how rendaku can ' t happen. This research uses the technique collecting data such as jitsurei and sakurei. Data collected are verbal results reduplication and also words results composition which experienced rendaku and who also failed to undergo rendaku. Based on the conclusions this research result there some things can be inferred. On reduplication, change the sound can occur only if the word is wago and in one component of the word consisting of two mora. While in composition, if composition of kango Word, the first component influential against an onset of rendaku. Where components have the influence of nasal sounds (nasal). Keywords : Rendaku, Reduplication, Composition